von Willebrand disease type 2A phenotypes IIC, IID and IIE: A day in the life of shear-stressed mutant von Willebrand factor - Brehm, Maria A.; Huck, Volker; Aponte-Santamaría, Camilo; Obser, Tobias; Grässle, Sandra; Oyen, Florian; Budde, Ulrich; Schneppenheim, Sonja; Baldauf, Carsten; Gräter, Frauke; Schneider, Stefan W.; Schneppenheim, Reinhard (Thrombosis and Haemostasis, 2014)
The bleeding disorder von Willebrand disease (VWD) is caused by mutations of von Willebrand factor (VWF), a multimeric glycoprotein essential for platelet-dependent primary haemostasis. VWD type 2A–associated mutations each disrupt VWF biosynthesis and function at different stages, depending on the VWF domain altered by the mutation. These effects cause considerable heterogeneity in phenotypes and symptoms. To characterise the molecular mechanisms underlying the specific VWF deficiencies in VWD 2A/IIC, IID and IIE, we investigated VWF variants with patient-derived mutations either in the VWF pro-peptide or in domains D3 or CK. Additionally to static assays and molecular dynamics (MD) simulations we used microfluidic approaches to perform a detailed investigation of the shear-dependent function of VWD 2A mutants. For each group, we found distinct characteristics in their intracellular localisation visualising specific defects in biosynthesis which are correlated to respective multimer patterns. Using microfluidic assays we further determined shear flow-dependent characteristics in polymer-platelet-aggregate formation, platelet binding and string formation for all mutants. The phenotypes observed under flow conditions were not related to the mutated VWF domain. By MD simulations we further investigated how VWD 2A/IID mutations might alter the ability of VWF to form carboxy-terminal dimers. In conclusion, our study offers a comprehensive picture of shear-dependent and shear-independent dysfunction of VWD type 2A mutants. Furthermore, our microfluidic assay might open new possibilities for diagnosis of new VWD phenotypes and treatment choice for VWD patients with shear-dependent VWF dysfunctions that are currently not detectable by static tests.
Keywords: von Willebrand factor; VWD; shear flow; microfluidic; molecular dynamics simulations